1991
DOI: 10.1002/anie.199111601
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Effects on Geometry and Chemical Shifts. An Ab Initio/IGLO Reconciliation of Apparent Experimental Inconsistencies on H3B · NH3

Abstract: To what extent can the structural parameters of a molecule be altered by the surrounding medium? According to model calculations in a polar solvent continuum, the BN bond length in H3B. NH3 in aqueous solution is indicated to be shortened by ca. 0.1 Å over the value in the gas phase (1.672 Å, microwave), i.e. to nearly the BN separation in the solidstate (1.564 Å, X‐ray). Similar calculations with the solvent hexane gave a value of 1.62 Å.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(44 citation statements)
references
References 28 publications
5
39
0
Order By: Relevance
“…The same has been surmised in other cases, for instance for d( 11 B) in aqueous BH 3 ÀNH 3 . [44] To be on the safe side, however, point charges were included in the subsequent chemical-shift evaluations in water.…”
Section: Resultsmentioning
confidence: 99%
“…The same has been surmised in other cases, for instance for d( 11 B) in aqueous BH 3 ÀNH 3 . [44] To be on the safe side, however, point charges were included in the subsequent chemical-shift evaluations in water.…”
Section: Resultsmentioning
confidence: 99%
“…[52] More often, however, such direct effects are small and can be superseded by "indirect" effects, that is, by changes in the molecular geometry on solvation. [53] These latter effects (which could be modeled by optimizing the geometry in the presence of a continuum) are expected to be small for 1, given the slight sensitivity of the computed d( 11 B) values toward the details of the geometrical parameters (see above). Thus, a single-point PCM calculation was performed for the gas-phase BP86/AE1 geometry.…”
Section: B: When Comparing the D(mentioning
confidence: 99%
“…The observed B1 N1 distance can be compared well with the value of 1.565Å in ammonia-borane [15], 1.564Å in hydrazine-borane [23], and 1.600Å in ethylenediamine-bis(borane) [24]. From a CSD (Cambridge Structural Database) [25] search, it has been found that this distance is longer for the complexes with secondary amines (in the range 1.61-1.62Å) and tertiary amines (in the range 1.61-1.66Å), in spite of the increasing gas-phase basicity in the series N 2 H 4 < NH 3 < NH 2 R < NHR 2 < NR 3 .…”
Section: X-ray Analysismentioning
confidence: 77%
“…Except for the longer distance B N (1.658Å), the calculated structural parameters for 1a in the gas phase are close to those determined by X-ray structural analysis in the solid state (see Table 2). In the case of the ammoniaborane adduct H 3 N BH 3 , the B3LYP/6-311++G calculated distance B N (1.671Å) is also longer than the distance experimentally determined (1.565Å [15]). The Gaussian 98 implementation of the gaugeindependent atomic orbital (GIAO) method for calculating nuclear magnetic shielding tensors at both HF and DFT levels [16] was successfully employed (vide infra).…”
Section: Infrared Spectrum and Computational Partmentioning
confidence: 78%
See 1 more Smart Citation